2021
DOI: 10.3390/vaccines9020076
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of mRNA Vaccine against SARS-CoV-2 Using a Polyglucin:Spermidine Conjugate

Abstract: One of the key stages in the development of mRNA vaccines is their delivery. Along with liposome, other materials are being developed for mRNA delivery that can ensure both the safety and effectiveness of the vaccine, and also facilitate its storage and transportation. In this study, we investigated the polyglucin:spermidine conjugate as a carrier of an mRNA-RBD vaccine encoding the receptor binding domain (RBD) of the SARS-CoV-2 spike protein. The conditions for the self-assembling of mRNA-PGS complexes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
(60 reference statements)
0
20
0
2
Order By: Relevance
“…Towards this end, the Fusogenix platform has been specifically designed, which represents a mixture of neutral lipids and small membrane proteins involved in membrane fusion. Although the toxicity of such liposomes appears to be significantly lower, they are still not devoid of certain important drawbacks both related to the liposomes themselves and the technically challenging transportation and storage of such vaccines which require cold chain maintenance [ 16 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Towards this end, the Fusogenix platform has been specifically designed, which represents a mixture of neutral lipids and small membrane proteins involved in membrane fusion. Although the toxicity of such liposomes appears to be significantly lower, they are still not devoid of certain important drawbacks both related to the liposomes themselves and the technically challenging transportation and storage of such vaccines which require cold chain maintenance [ 16 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was incubated for 2 more hours and the target product was purified from the unreacted components by gel-filtration in PBS-equilibrated G-25 Sefadex. To form the DNA–PGS complexes, DNA was mixed with PGS in a 1 : 10 mass ratio [ 15 , 16 ], and the product yield was assessed by the changes in the DNA electrophoretic mobility in 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More research continues in the field of the delivery of mRNA vaccines, suggesting that, along with liposomes, other components could serve as coadjuvants. An example recently studied in mice is a conjugate of polyglucan and spermidine, with a positive charge, which aids in enveloping negatively charged mRNA [ 109 ].…”
Section: Vaccines In Clinical Developmentmentioning
confidence: 99%
“…Many studies [ 18 , 19 ] have demonstrated that mRNA-based vaccines are a promising platform with such useful features as flexibility, scalability, cheap production, and independence from the cold chain [ 15 ]. Due to the possibility of making a simple change to the target gene in an mRNA vaccine without modifying production technology, one can quickly respond to the emergence of new pandemic infectious agents, especially the influenza virus.…”
Section: Introductionmentioning
confidence: 99%